2023
DOI: 10.3389/fpls.2023.1207762
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of in vitro and ex vitro Agrobacterium rhizogenes-mediated hairy root transformation of soybean for visual screening of transformants using RUBY

Abstract: In vitro and ex vitro Agrobacterium rhizogenes-mediated hairy root transformation (HRT) assays are key components of the plant biotechnology and functional genomics toolkit. In this report, both in vitro and ex vitro HRT were optimized in soybean using the RUBY reporter. Different parameters including A. rhizogenes strain, optical density of the bacterial cell culture (OD600), co-cultivation media, soybean genotype, explant age, and acetosyringone addition and concentration were evaluated. Overall, the in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Induced hairy roots transformation through R. rhizogenes has been considered as genotype-independent approach to generate transgenic root that no significant difference in hairy root induction frequency were observed among tested cultivars (Fan et al, 2020;Cheng et al, 2021;Zhou et al, 2022). However, several reports recently indicated that genotype is a critical factor effect the transformation efficiency in R. rhizogenes mediated hairy root transformation (Aggarwal et al, 2018;Xu et al, 2020;Niazian et al, 2023). Thus, our results suggested that genotype is a critical factor should be considered to examine before establish R. rhizogenes mediated hairy root transformation in mung bean.…”
Section: Resultsmentioning
confidence: 99%
“…Induced hairy roots transformation through R. rhizogenes has been considered as genotype-independent approach to generate transgenic root that no significant difference in hairy root induction frequency were observed among tested cultivars (Fan et al, 2020;Cheng et al, 2021;Zhou et al, 2022). However, several reports recently indicated that genotype is a critical factor effect the transformation efficiency in R. rhizogenes mediated hairy root transformation (Aggarwal et al, 2018;Xu et al, 2020;Niazian et al, 2023). Thus, our results suggested that genotype is a critical factor should be considered to examine before establish R. rhizogenes mediated hairy root transformation in mung bean.…”
Section: Resultsmentioning
confidence: 99%
“…A visual identification technology system for gene-edited soybeans was established by utilizing RUBY as a reporter system, and transgene-free genetically edited soybean plants were successfully obtained through seed and cotyledon color [14]. Therefore, RUBY can be used as a new visual reporting system [12,15,16]. In this study, RUBY was introduced into a binary expression vector as a reporter in A. rhizogenes-mediated hairy root genetic transformation in L. corniculatus.…”
Section: Introductionmentioning
confidence: 99%
“…This system can express a single open reading frame of 2A peptide-linked betalain biosynthesis genes using a single promoter and can be used for gene expression monitoring and plant transformation. For example, RUBY was utilized for betalain engineering in various crops, including carrot [ 29 ], cotton [ 30 ], cannabis [ 31 ], soybean [ 32 ], and poplar [ 33 ]. The RUBY reporter is also used as a biotechnological tool; for example, for efficient haploid identification in maize and tomatoes [ 34 ] and genome editing in soybeans as a visual indicator [ 35 ].…”
Section: Introductionmentioning
confidence: 99%